Evaluation of Risk Factors for Early Insufficiency after Bronchial Sleeve Resections - Levchenko, Evgeny; Shabinskaya, Viktoriia; Levchenko, Nikita; Mikhnin, Alexander; Mamontov, Oleg; Ergnyan, Stepan (The Thoracic and Cardiovascular Surgeon, 2024)
Background Bronchoplastic resections are now widely used as a surgical treatment for resectable central lung cancer. However, bronchial dehiscence is one of the most life-threatening complications, making it important to identify its risk factors to separate patients who require more attention during the postoperative period.Methods The data of 285 patients who underwent bronchoplasty from 2006 to 2021 were retrospectively reviewed. We collected demographic characteristics, history of neoadjuvant therapy, preoperative assessment, perioperative outcomes, and postoperative complications to investigate different variables as risk factors for bronchial dehiscence by univariate and multivariate analyses.Results Bronchial dehiscence was diagnosed in 12 patients (4.2%) with a mean presentation on postoperative day 10 (range: 1–24 days). By multivariate analysis, current smoking (odds ratio [OR]: 4.8, 95% confidence interval [CI]: 1.1–20.1, p = 0.032), chronic obstructive pulmonary disease (COPD; OR: 6.5, 95% CI: 1.2–33.8, p = 0.027), bronchoplastic right lower lobectomy (OR: 12.9, 95% CI: 2.4–69.7, p = 0.003), and upper sleeve bilobectomy with segmentectomy S6 by performing an anastomosis between right main bronchus (RMB) and bronchus of basal pyramid (BP) (OR: 30.4, 95% CI: 3.4–268.1, p = 0.002) were confirmed as relevant risk factors for developing bronchial dehiscence.Conclusion Current smoking, COPD, bronchoplastic right lower lobe, and upper l with segmentectomy S6 by performing an anastomosis between RMB and bronchus of BP were identified with the occurrence of bronchial dehiscence after sleeve resection.
Keywords: lung cancer treatment (surgery medical); surgery; complications